Analisis Sikap Mahasiswa dalam Menyikapi Konflik Perbedaan Pendapat Antar Teman Sebaya - Ramadhan, Trisno Adin; Winingsih, Evi; Purwoko, Budi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine how students handle disagreements with their peers in classroom settings. Although conflict is considered a normal part of social interaction, inappropriate conflict management can lead to interpersonal tension. This research employed a descriptive qualitative method with purposive sampling. Three students aged 21–22 years served as informants and were interviewed in depth. Data were collected through semi-structured interviews, field notes, and supporting documentation. The data were then analyzed narratively based on five aspects: communication patterns in conflict situations, emotional attitudes toward conflict, resolution techniques, psychological and relational effects, and social values and attitudes toward differences. The findings indicate that in handling disagreements, students generally demonstrate openness, assertiveness, and empathy. They are able to manage negative emotions, seek resolution strategies based on cooperation and compromise, and view differences as opportunities for social learning. Conflicts tend to be constructive, as they are approached with self-reflection and efforts to maintain positive relationships. Students’ adaptive attitudes toward conflict are strongly influenced by their emotional intelligence and interpersonal communication skills. Overall, the study concludes that students display social and emotional maturity in dealing with disagreements, which helps foster a positive and inclusive communication culture on campus.